Self-addressed questions and honorifications : The case of Japanese daroo-ka/desyoo-ka - Chang, Chen-An (My University, 2022)
Japanese self-addressed questions (SAQs) are either marked with SAQ question particles (i.e. kana, yara) or marked with modals daroo or desyoo. The present paper argues that the pragmatic profile of Japanese SAQs should not be limited to solitary contexts. The paper presents an experiment examining whether daroo-ka/desyoo-ka can be perceived as SAQs in the accompanied contexts. The results of the experiment indicate that Japanese SAQs can be felicitously uttered in the presence of a second (socially higher) person. Apart from the experimental study, this paper also presents a pilot study of comparing daroo-ka questions and plain information-seeking questions (i.e. those without daroo-ka) in urgent situation contexts. The preliminary results shed light on the fact that Japanese native speakers interpret daroo-ka questions as canonical questions in the performance of indirect speech acts.
Keywords: self-addressed questions; urgent questions; honorifics; contexts; speech acts; 400